A RESPONSIVE THEORY OF JUDICIAL REVIEW - Astik, Niki Rajendrakumar; Paramar, Daxa B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As used in India, the Responsive Theory of Judicial Review stresses how important it is for judicial review to be aware of the Indian court’s unique institutional position and abilities, as well as the Indian legal system’s specific conditions and constraints. This way of thinking goes beyond the strict Indian perspective of judicial supremacy and calls for a more nuanced and careful use of judicial review. It requires thinking about the subtleties of public interest litigation in India and the possibility of legislative dysfunction. According to a responsive approach, judicial review in India is complicated and needs to take into account the courts’ institutional limits and how it can affect other branches of government, all while still following democratic values and constitutional norms.